Innovative Work Behavior Strengthening Model: Role of Self-Efficacy, Knowledge Sharing, and Organisational Creative Climate as Predictors - Indajang, Kevin; Sembiring, Lenny Dermawan; Sherly, Sherly; Efendi, Efendi; Sudirman, Acai (Valid: Jurnal Ilmiah, 2023)
This study aims to analyze the model of reinforcing innovative work behavior regarding self-efficacy, knowledge sharing, and organizational creative climate as predictors. The population in this study comes from primary data obtained from the field, namely MSME players in the Lake Toba Tourism area. The sampling method used in this research is the convenience sampling method. The number of samples analyzed was 170 MSME actors. Data collection techniques use observation, interviews, questionnaires, and documentation. The data analysis method used is Partial Least Square (PLS). The results of the data analysis concluded that self-efficacy, knowledge sharing, and organizational creative climate had a positive and significant effect on innovative work behavior. The implication of this research is measuring the level of innovative work behavior within organizations, identifying trends of change over time, and measuring the level of self-efficacy, knowledge sharing, and organizational creative climate within organizations regularly. In addition, MSME actors can provide constructive feedback on employee performance in self-efficacy, knowledge sharing, and organizational creative climate. This condition can help employees improve their ways of innovating at work.